Um outro conceito de novo: o bairro do Comércio na modernização do Porto de Salvador (1912-1933). - Silveira De Paoli, Dra. Arq. Paula (Universidad Nacional del Litoral, 2014)
This study aims to analyze the effects of modernization of the Port of Salvador in the Commercial District, through the architecture produced between 1912 and 1933. The renewal of the district of Comércio was part of the modernization of the Port of Salvador, and consisted in the enlargement of nearly every street in the existing part of the district in 1912, and in the construction of a wide strip of embankment that separated the district from the warehouses of the new port. The research allowed to point out that this process of modernization took place within a culture which sought to build dialogue with the past in the production of the new architecture. This is visible both in the conservation and use of the existing buildings, when the streets were enlarged, and in the difficulty of occupying the strip of embankment, which remained a major urban void during the whole period of the study.